Supernatural or Material: Haunted Places in H.P. Lovecraft’s, M.R. James’s, A. Machen’s and A. Blackwood’s Horror Fiction - Maleszka, Anna; Maleszka, Mateusz (Theoria et Historia Scientiarum, 2017)
The horror story writers of the early 20th century presented various views on the surrounding reality. Howard P. Lovecraft and Montague R. James, for their part, rejected the mere possibility of phenomena regarded as supernatural, contrary to other writers, such as Arthur C. Doyle, Arthur Machen or Algernon Blackwood, who were members of theosophical or occultist societies. The writers differed also in the level of their education. Lovecraft was an erudite interested in science, notwithstanding the fact that he did not receive formal education. James was a respected medievalist, a specialist in the history of Christianity. Blackwood, educated abroad (in Germany), explicitly differed in his artistic output from Machen, a Welshman, who left the United Kingdom only to pursue his journalistic career. The aim of the article is to present the haunted places in the literary works of the chosen authors and to juxtapose their narratives with their scholarly achievements and their views on the surrounding reality. Based on the New Historicist approach, the study shows that the roots of horror in the haunted places presented by the authors in their works were more “material” than “supernatural”—what accounted for their choices of haunted places, story characters and haunting horrors were personal attitudes and life experience of each of the writers.